Metamorphic processes and seismicity: The Bergen Arcs as a natural laboratory - Putnis, Andrew; Jamtveit, B.; Austrheim, H. (Oxford University Press, 2017)
In the Bergen Arcs rocks that formed the root zone of the Caledonian mountain chain formed by the collision of Laurentia and Baltica at ~400 Ma are exposed. They display a well-exposed, highgrade metamorphic terrane where Sveconorwegian granulites and Caledonian eclogite and amphibolite parageneses coexist spatially and provide challenging problems related to their interrelationships and their geodynamic settings. Some of the ideas that have been proposed for the formation of the granulites and the mechanism of their retrograde hydration during the Caledonian orogeny are reviewed. We make some preliminary microstructural observations on the earliest stages of retrogression and suggest that much progress in understanding metamorphism in terranes such as the Bergen Arcs could be made by greater attention to the relationship between seismicity and metamorphism. The Bergen Arcs provide a natural laboratory in which it should possible to elucidate the extent to which seismicity and cataclasis are a necessary precursor to fluid infiltration and metamorphism, the volume of rock processed by cataclasis during an orogenic event and the role of deviatoric stress in the metamorphic reactions.